Comparing the efficacy of pulsed dye laser, Q-Switched Nd-YAG, CO2, and combined CO2 and Q-Switched Nd-YAG lasers for the treatment of cutaneous macular amyloidosis. (17th February 2021) - Radmanesh, Mohammad; Ghanatir, Forough; Radmanesh, Ramin
Abstract: Background: No topical and systemic treatment is proven to be effective on Cutaneous Macular Amyloidosis (CMA). The physical removal of the deposited protein by lasers may be a better choice. Objective: To compare the efficacy of different lasers including Pulsed dye laser (PDL), 1064 mode of Q-Switched Nd-YAG, CO2, and combined CO2 and Q-Switched Nd:YAG lasers for the treatment of CMA. Patients and Method: 17 adult female patients with clinical CMA and histopathological confirmation were included in this study. Four close 1 by 1 cm 2 areas were treated simultaneously with PDL, Q-Switched Nd-YAG, CO2 and combined CO2 and Nd-YAG Lasers. The energy used for 585 nm PDL were 9 J/cm 2 with the spot size of 5 mm. The energy used for 1064 nm mode of Nd-YAG laser was 5 Joules/cm 2, with the spot size of 4 mm, and the frequency of 10 hertz. The energies used for CO2 laser were 4 and 3.5 Micro Joules for the first and second Passes. Results: No desirable result obtained after PDL therapy. The Q-Switched Nd-YAG was effective in only 3 patients. All areas treated with CO2 laser were cleared. Conclusion: The CO2 laser is seems to be the most effective laser treatment of CMA.